2019
DOI: 10.1016/j.semarthrit.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of positive 18F-FDG PET/CT-scan for large vessel vasculitis in patients with persistent polymyalgia rheumatica

Abstract: Inflammatory low back pain, pelvic girdle and diffuse lower limb pain are predictors of positive PET/CT scan for LVV in PMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 37 publications
4
49
4
Order By: Relevance
“…8 In recent years, the advent of new imaging techniques has revealed that GCA can also affect extracranial large vessels, even in the absence of classic cranial GCA symptoms. 13 GCA patients with predominant extracranial large vessel affection are usually younger at diagnosis and present more commonly with refractory features of PMR, fever of unknown origin, constitutional symptoms, and/or limb claudication. [14][15][16] Cutaneous manifestations are uncommon in GCA and are rarely found as the presenting symptom of GCA.…”
Section: Introductionmentioning
confidence: 99%
“…8 In recent years, the advent of new imaging techniques has revealed that GCA can also affect extracranial large vessels, even in the absence of classic cranial GCA symptoms. 13 GCA patients with predominant extracranial large vessel affection are usually younger at diagnosis and present more commonly with refractory features of PMR, fever of unknown origin, constitutional symptoms, and/or limb claudication. [14][15][16] Cutaneous manifestations are uncommon in GCA and are rarely found as the presenting symptom of GCA.…”
Section: Introductionmentioning
confidence: 99%
“…Persistently elevated levels of CRP and IL-6 during follow-up have been associated with an increased risk of relapse and recurrence (that is, flare of PMR after discontinuation of glucocorticoid treatment) 47 . Whether some of these patients had underlying GCA is unknown; however, imaging studies reported a high prevalence of underlying LVV in patients with PMR with recurrent flares 114,115 . Surprisingly, patients with PMR who had subclinical LVV according to PET at baseline responded equally well to 15 mg daily prednisone and had a similar frequency of relapses to patients without vascular FDG uptake 103 .…”
Section: Long-term Management Predictors Of Disease Coursementioning
confidence: 99%
“…A recent study showed that many patients thought to have isolated polymyalgia rheumatica, without associated cranial symptoms, often have evidence of LVV on FDG-PET. [50] These studies indicate that PET has good sensitivity for detecting vascular inflammation, but its imperfect specificity highlights that vascular PET activity may be present in other conditions, particularly atherosclerosis, and can be similar to LVV on imaging. Other limitations to PET include cost, radiation exposure, limitations to access, and lack of a standardized approach for analysis of vascular activity.…”
Section: Suspected Tak or Gca With Predominantly Large-artery Involvementmentioning
confidence: 98%